40 Jahre Institut für Politikwissenschaft an der Leopold-Franzens-Universität Innsbruck Eine Festschrift - Senn, Martin (innsbruck university press, 2018)
The Department of Political Science at the University of Innsbruck celebrated the 40th anniversary of its founding in 2017. This Festschrift takes stock of the department's past and present from professional and personal perspectives, and identifies challenges and perspectives for its future development. The authors address milestones in the foundational phase of the department, the transformation in human resources and infrastructure, and changes in the culture of research and study programs at the department. These perspectives multiple insights into the experiences of colleagues and students at our department.